Squatters and the Law - Teo, Keang Sood (Journal of Malaysian and Comparative Law, 2019)
In the English Court of Appeal case of McPhail v Persons, Names Unknown, the Master of Rolls, Lord Denning, defined a "squatter" as "one who, without any colour of right, enters on an unoccupied house or land, intending to stay there as long as he can." An examination of decided case law and the relevant legislation have not been prepared to endorse any social or political justification for the dispossession of a rightful owner of his land. The idea that the existing distribution of law may itself express or conceal inequity is not a notion which the courts have been ready to explore.